Pre-Designed Tetrasodium Pyrophosphate Plant from Sodium Hydroxide and Phosporic Acid Using Two-Stage Process with Pre-Treatment Neutralization with Capacity 44.000 ton/year - CITRA WIDIYAWATI (Institut Teknologi Adhi Tama Surabaya, 2022)
Tetrasodium pyrophosphate (Na4P2O7) is an inorganic caompound used in the detergent manufacturing industry as a buider or stain remover. In addition, TSPP can also be used in the paint industry, construction industry, ceramic industry, and the culinary world. The location of the tetrasodium pyrophosphate factory is planned to be established in Gresik sub-district, Gresik district, East Java, which is south of tha Java Sea. Its strategic location which is closes to factories that supply raw materials such as PT. Tjiwi Chemistry. Beside that, its location is in an Industrial Estate so that it can support the utility section. The availability of empty land that is still wide allows for expansion of the factory for the future. The form of this company is a Limited Liability Company (PT) with line and staff organizational structure. A lot employees as many as 300 people. From the results of the economic analysis, the Internal Rate of Return (IRR) is 34,845%, the Pay of Time (POT) is 2,972 years, and the Break Even Point (BEP) is 33,02%. Based of the determined economic analysis, Tetrasodium pyrophosphate from sodium hydroxide and phosphoric acid is feasible to be established.